2016
DOI: 10.1111/jgs.14735
|View full text |Cite
|
Sign up to set email alerts
|

Balance and Mobility in Community‐Dwelling Older Adults: Effect of Daytime Sleepiness

Abstract: Self-reported daytime sleepiness is associated with slower gait speed and poor balance confidence in community-dwelling older adults. Subjective sleep assessment should be considered when assessing balance and implementing interventions for improving balance in older adults. Further study is needed to examine the role of CNS medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
(109 reference statements)
1
12
0
Order By: Relevance
“…In our study almost one quarter of participants often or always had sleeping problems and almost half sometimes experienced such problems. A recent study has shown that poor sleep plus daytime sleepiness is related to walking speed and self-reported balance [ 53 , 54 ]. Sleep disorders are common among older people [ 27 ], related to mobility problems and falls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study almost one quarter of participants often or always had sleeping problems and almost half sometimes experienced such problems. A recent study has shown that poor sleep plus daytime sleepiness is related to walking speed and self-reported balance [ 53 , 54 ]. Sleep disorders are common among older people [ 27 ], related to mobility problems and falls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults who report daytime sleepiness from sleep disorders have slower gait speed and decreased confidence in balance when walking (Tyagi et al, 2017), which can contribute to fear of falling (Chang, Chen, & Chou, 2016). Falls are also a risk in patients who complain of poor sleep quality or sleep disturbance (Stone et al, 2014), particularly when taking sleep medicine (Min, Kirkwood, Mays, & Slattum, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Functional domain: Sleep disorders and poor sleep are associated with impaired functional status (Loh et al, 2017;Song, Dzierzewski, et al, 2015), poor gait, lack of confidence in balance (Tyagi, Perera, & Brach, 2017), and poor grip strength (Jeong et al, 2017). Sleep disorders affect muscle mass and functioning, which can translate into poor physical performance (Auyeung et al, 2015).…”
Section: Problems Associated With Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Myotonic dystrophy type 1 and 2 (DM1/DM2) are genetic multisystem disorders with varying symptoms, including muscle weakness, myotonia, cardiac arrhythmias and brain dysfunction [1][2][3][4][5] . Recognized risk factors for falling in DM1 include distal and/or proximal muscle weakness, myotonia, cognitive impairment and daytime sleepiness [6][7][8][9][10][11][12][13] . We recently performed a randomized clinical trial to test the effect of cognitive behavioral therapy including a physical training module on fatigue in DM1, and found that falling incidence, circumstances and consequences of falls in a large cohort of adult patients with DM1 and DM2 compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%